Is the strength of direct antiglobulin test important for the duration of phototherapy?. (March 2014) - Oztekin, Osman; Kalay, Salih; Tezel, Gonul; Barsal, Ebru; Bozkurt, Selen; Akcakus, Mustafa; Oygur, Nihal
Abstract The purpose of this study was to evaluate the relationship between the grades of positivity of the direct antiglobulin test (DAT) and their effects on the duration of phototherapy for neonatal jaundice. DAT reactions of blood samples were graded as (1+), (2+), (3+) and (4+). DAT was positive in 80 neonates who were exposed to phototherapy due to jaundice. Patients with positive DAT reactions are classified in the study as follows: 34 newborns were DAT (1+), 18 newborns were DAT (2+), 16 newborns were DAT (3+) and 12 newborns were DAT (4+). We found that higher grades of positivity of DAT are associated with extended duration of phototherapy (r = 0.436, p < 0.05). Additionally, DAT (4+) reactions are more predictive for a prolonged duration of phototherapy requirement than the other grades (p < 0.0001).